Application of Mnemonics Learning Strategies with Cooperative Learning Models to Improve Mastery of Human Digestive System Concepts: Class VIII H Students of SMP Negeri 5 Kendari - Masdiana (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2021)
This study aims to determine the mnemonics learning strategy in increasing the mastery of the concept of the human digestive system through a direct learning model for Class VIII H students of SMP Negeri 5 Kendari. This research was conducted in class VIII H at SMP Negeri 5 Kendari, the odd semester of the 2019/2020 academic year, to be exact, from October to November 2019. The total number of students is 35 consisting of 20 female students and 15 male students. This classroom action research procedure consists of 2 (two) cycles. Each cycle is carried out by the indicators to be achieved from the factors being investigated, which are carried out in stages: (1) planning; (2) implementation of the action (action); (3) Observation and Evaluation (observation and evaluation); and (4) reflection. The results showed that direct learning methods applied through mnemonics techniques could improve students' mastery of learning concepts in human digestion material, which was reflected in the results of evaluating participation, cooperation, ability, and making conclusions have increased.